On CNU, The Thirty-Year War, and the Environment (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Dan Solomon writes beautifully; clever, sharp, pithy, but never snide. His prose is so deliciously accessible, however, that the full force and power of his underlying polemic can sometimes be overlooked. Such is especially the case, I believe, with his essay: “CNU: The Thirty-Year War—New Urbanism and the Academy” (Chapter 17 in Housing and the City: Love Versus Hope). Almost hidden within this essay is a very important urban argument deserving special attention. Solomon’s argument, however, is cloaked in an entertaining introductory discussion of CNU versus the Academy, and only emerges about half-way through the essay. In the beginning, he toys with the Academy and CNU like a cat with two mice: the Academy for narcissistically chasing only anti-urban, one-off, goofy buildings which can’t make urbanism; and CNU for devolving into the production of dreary fabric without inventive architecture. He then posits “A Third Way,” where urban fabric is enlivened by inventive civic architecture embedded in dense urban fabric. This requires real cities, however, and Solomon eloquently cites examples in Rome and San Francisco, thus challenging both CNU and the Academy to develop urbanity rather than suburbs and narcissistic architecture. The current environmental crisis injects unavoidable urgency into Solomon’s argument because cities are the most efficient form of human habitation by consuming less energy and producing less carbon on a per capita basis.